Diseño de patrones y su incidencia en la enseñanza en corte y confección de vestidos de gala dirigidos a la comunidad de la Isla Puná “Barrio Lindo” cantón Guayaquil provincia del Guayas - Castro Moreira, Mary Mery (2017)
The purpose of this thesis is to provide training to persons who feel the desire of overcoming labour, through workshops in the short and medium term students to develop their interests in becoming competitive in the area of clothing. "The garment industry" by means of which manage to have an improvement in quality of life within the family nucleus. And his community, all industry productive is linked to knowledge skills and abilities which help the development of the different areas undertaken by man, in other words these are competencies that are determined in a specific profile for the different activities of the broad field of labor. Productive sectors and socio-economic performance. Through which dominate decision-making, activates creativity and seeks solutions to incidental problems that could arise within the learning process, activate personal and at the same time of resource management to organize and coordinate participatory groups with the aim of making workshops programs preserve reliable and fruitful to improve the quality of life inside and outside the community. This training plan aims to facilitate viable tools and sustainable improvement in the not distant future, with the manifestation of their learning acquired as a faithful witness to their community.